Targeting cancer metabolism breaks radioresistance by impairing the stress response - Schwab, Melissa; Thunborg, Katharina; Azimzadeh, Omid; Von Toerne, Christine; Werner, Caroline; Shevtsov, Maxim; Di Genio, Tommaso; Zdralevic, Masa; Pouyssegur, Jacques; Renner, Kathrin; Kreutz, Marina; Multhoff, Gabriele (Cancers, 2021)
The heightened energetic demand increases lactate dehydrogenase (LDH) activity, the corresponding oncometabolite lactate, expression of heat shock proteins (HSPs) and thereby promotes therapy resistance in many malignant tumor cell types. Therefore, we assessed the coregulation of LDH and the heat shock response with respect to radiation resistance in different tumor cells (B16F10 murine melanoma and LS174T human colorectal adenocarcinoma). The inhibition of LDH activity by oxamate or GNE-140, glucose deprivation and LDHA/B double knockout (LDH−/−) in B16F10 and LS174T cells significantly diminish tumor growth; ROS production and the cytosolic expression of different HSPs, including Hsp90, Hsp70 and Hsp27 concomitant with a reduction of heat shock factor 1 (HSF1)/pHSF1. An altered lipid metabolism mediated by a LDHA/B double knockout results in a decreased presence of the Hsp70-anchoring glycosphingolipid Gb3 on the cell surface of tumor cells, which, in turn, reduces the membrane Hsp70 density and increases the extracellular Hsp70 levels. Vice versa, elevated extracellular lactate/pyruvate concentrations increase the membrane Hsp70 expression in wildtype tumor cells. Functionally, an inhibition of LDH causes a generalized reduction of cytosolic and membrane-bound HSPs in tumor cells and significantly increases the radiosensitivity, which is associated with a G2/M arrest. We demonstrate that targeting of the lactate/pyruvate metabolism breaks the radioresistance by impairing the stress response.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Lactate/pyruvate metabolism; LDHA/B double knockout; Membrane heat shock protein 70 (Hsp70); Radiosensitivity; Stress response